(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
By the end of the twentieth century, the status of a language of world importance was finally strengthened in English. Today, the ability to know foreign languages is becoming one of the integral parts of professional education. This article is about the rational use of modern innovative technologies in teaching English, which is one of the world’s languages, and rapid teaching by using tried and tested methods. required information is provided.